TECHNIQUES TO EVALUATE AND COMBINE CULTURAL ERRORS IN UZBEK AND ENGLISH - Saparova Dilafruz Muxiddin qizi; G. Ro’ziyeva (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article explores effective techniques for evaluating and combining cultural errors  in  Uzbek  and  English  communication.  Cultural  differences  often  lead  to misunderstandings,  particularly  when  language  nuances,  idiomatic  expressions,  or societal  norms  are  misinterpreted.  The  paper  highlights  key  methods  such  as comparative  cultural  analysis,  error  categorization,  and  cross-cultural  training  to minimize and address these errors. Practical solutions are proposed to bridge cultural gaps, fostering effective communication and mutual understanding between Uzbek and English speakers in various social, educational, and professional contexts.